1993
DOI: 10.1007/bf00351494
|View full text |Cite
|
Sign up to set email alerts
|

Saccharomyces cerevisiae phosphoglucose isomerase and fructose bisphosphate aldolase can be replaced functionally by the corresponding enzymes of Escherichia coli and Drosophila melanogaster

Abstract: Two glycolytic enzymes, phosphoglucose isomerase and fructose-1,6-bisphosphate aldolase, of Saccharomyces cerevisiae could be replaced by their heterologous counterparts from Escherichia coli and Drosophila melanogaster. Both heterologous enzymes, which show respectively little and no sequence homology to the corresponding yeast enzymes, fully restored wild-type properties when their genes were expressed in yeast deletion mutants. This result does not support notions of an obligatory formation of glycolytic mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
29
0

Year Published

1993
1993
2017
2017

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 39 publications
3
29
0
Order By: Relevance
“…4; Cabib and Leloir, 1958;Vandercammen et al, 1989;Londesborough and Vuorio, 1991). However, even at only 1 mM phosphate, the concentration of Fru6P for half-maximal activation (1.4 mM), is higher than the bulk concentration of Fru6P in yeast ( 5 0.1 -0.7 mM; Lagunas and Gancedo, 1983;Boles and Zimmerman, 1993). FranSois et al (1991) reported that the sum of Glc6P and Fru6P was only 0.4 mM during trehalose accumulation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…4; Cabib and Leloir, 1958;Vandercammen et al, 1989;Londesborough and Vuorio, 1991). However, even at only 1 mM phosphate, the concentration of Fru6P for half-maximal activation (1.4 mM), is higher than the bulk concentration of Fru6P in yeast ( 5 0.1 -0.7 mM; Lagunas and Gancedo, 1983;Boles and Zimmerman, 1993). FranSois et al (1991) reported that the sum of Glc6P and Fru6P was only 0.4 mM during trehalose accumulation.…”
Section: Discussionmentioning
confidence: 99%
“…In this region, Glc6P and Fru6P concentrations may differ radically from their bulk cytosolic values. Finally, it is curious that the phenotype of yeast lacking phosphoglucoisomerase resembles that of cifl andfdpl mutants: both are characterized by poor growth in the presence of glucose and defective glucose-induced cAMP signalling, which cannot be completely explained by their over-accumulation of Glc6P and depletion of ATP (Bafiuelos and Fraenkel, 1982;Boles and Zimmerman, 1993). Possibly an appropriate Glc6PIFru6P ratio is required for the correct functioning of the 56-kDa polypeptide also in its role as a component of the cAMP signalling system.…”
Section: Discussionmentioning
confidence: 99%
“…Molecular techniques were performed according to published procedures (22). Yeast transformations and reisolation of plasmid DNA from yeast cells were carried out as described previously (6,11).…”
Section: Methodsmentioning
confidence: 99%
“…Molecular biology techniques were performed by using published procedures (25). Yeast transformations and reisolation of plasmid DNA from yeast cells were carried out as described previously (3,12).…”
Section: Methodsmentioning
confidence: 99%